Federalism and the Market for Corporate Control - Richard A. Booth (Washington University Law Quarterly, 1991)
Until 1987 the growing consensus was that the market for corporate control was distinctly interstate in character, and that only Congress and the Securities and Exchange Commission (SEC or Commission) had the authority to regulate it in any comprehensive way. All that quickly changed. In CTS Corp. v. Dynamics Corp. of America, the Supreme Court upheld the right of states to restrict takeovers of resident companies, and in Business Roundtable v. SEC, the D.C. Circuit Court of Appeals struck down the SEC's rule 19c-4, the Commission's most significant effort to curtail a wide range of takeover defenses by potential target companies, on the grounds that these defenses have the effect of reducing shareholder democracy. It might seem, to some observers at least, that the forces of darkness have prevailed in the war over takeover regulation. Most academic commentators hailed takeovers as a way of keeping management on its toes. On the other hand, potential target managers and their advocates saw takeovers as destructive, short-term strategies that amounted, at best, to the mere rearrangement of ownership interests and distracted business from its real objectives. To be sure, between the rise of state takeover statutes and the fall of rule 19c-4 corporate management is much more secure than it was. But that does not necessarily mean that the reason things turned out as they did is that the establishment usually wins. It may well be that both of these key decisions turn out to be eminently wise-both in terms of setting jurisdictional lines and in terms of substantive regulation.
Keywords: Federal government; Consolidation & merger of corporations